Pengaruh Literasi Keuangan, Pendapatan, Dan Perilaku Keuangan Terhadap Kepuasan Keuangan Petani Kecamatan Sakra Timur - Heri Gunawan; Susi Retna Cahyaningtyas; Widia Astuti (Fakultas Ekonomi dan Bisnis Unram, 2026)
This study investigates how financial literacy, income, and financial behavior affect the financial satisfaction of farmers in East Sakra District. Using a quantitative approach, data were collected through questionnaires from 150 farmers and analyzed with SmartPLS. The results reveal that financial literacy has no significant impact on financial satisfaction. In contrast, income and financial behavior show positive and significant effects. These findings highlight that adequate income and responsible financial management are key to achieving financial satisfaction among farmers, even when their understanding of financial concepts is limited. The model applied is both valid and reliable, with sufficient predictive capability. This research provides a valuable reference for local governments and stakeholders in designing effective programs to enhance farmer welfare through income improvement and better financial behavior.